Strategi Komunikasi Dinas Pariwisata Kulon Progo Dalam Program Sambang Kulon Progo (Sambanggo) Sebagai Upaya Peningkatan Pariwisata - Rizki Agung Fitriadi (Universitas Majalengka, 2023)
Good tourism management can increase tourist interest to visit, so tourism service businesses including the creative economy get benefit. This has a good impact on the economic condition of regional communities which has increased. Tourism with high demand can also contribute to Local Original Income. For this reason, Kulon Progo government through Kulon Progo tourism office with the sambanggo program needs a good communication strategy in order to manage tourism in Kulon Progo Regency well, considering currently tourism in Kulon Progo is trying to grow from the slump due to the Covid-19 pandemic. This aims of the study to determine communication strategy carried out by the Kulon Progo tourism office in the sambanggo program. This research was conducted using qualitative descriptive data analysis techniques, with data collection directly conducting observations, documentation, and interviews in the field to the head of field and the head of the Kulon Progo Tourism office. This research found that communication strategy used Kulon Progo tourism agency in the sambanggo program was hold various kinds of events or art performances at various tourism objects. In each event, there is jargon or yelling as a positive image formation. Kulon Progo tourism office also optimizes social media, news media, and official websites to disseminate information about the sambanggo program. Through the findings of this study, it is hoped that the government will be consistent in continuing to operate and develop a sustainable sambanggo program.